The Effect of ICV Administration of PI3K on Memory - Yaminifar, Zahra; Nasehi, Mohammad; Zarrindast, Mohammad Reza; Rohampour, Kambiz (Archives of Advances in Biosciences, 2019)
Introduction: Brain insulin receptors (IRs) have been suggested as an important regulatory factor for cognitive functions but the involvement of IR signaling in memory deficit associated with neurodegenerative conditions is not yet explored. Among the diverse signaling pathways of IR, PI-3 kinase and (MAP) kinase pathways in brain have been suggested for learning and memory functions. The phosphoinositide3-kinase (PI3K) complex plays important roles in virtually all cells of the body. The enzymatic activity of PI3Kto phosphorylate phosphoinositides in the membrane is mediated by a group of catalytic and regulatory subunits. Among those, the class I catalytic subunits, p110α, p110β,p110γ,and p110δ have recently drawn attention in the neuroscience field due to their specific dysregulation in diverse brain disorders. The present study was planned to investigate the effect of PI3K on memory. Materials and Methods: The animals were injected bilaterally with ICV water (control group), ICV PI3k (1,10 and 100 ng/rat) on days 1 and 3 after surgery. The learning and memory performance was assessed two weeks after the first dose of drugs by using step-through passive avoidance paradigm (0.3 mA, 3seconds) and open field test. The results revealed that The ICV administration of PI3K (P<0.05) altered inhibitory avoidance acquisition. PI3K at dose 1 ng/rat decreased the step- through latency during the retention test. Results: data showed that PI3K at dose of 1 ng/rat decreased the step- through latency during the retention test. In addition, the results showed that PI3K at dose 10 ng/rat increased locomotor activity. Conclusion: Finally, our data indicated that PI3K has critical role in memory consolidation and locomotor activity.